An exceptional metaplastic lobular breast carcinoma diagnosed through exome sequencing. Issue 9 (24th January 2020) - Bergeron, Anthony; Desmoulins, Isabelle; Beltjens, Francoise; Causeret, Sylvain; Charon-Barra, Celine; Martin, Etienne; Richard, Corentin; Boidot, Romain; Arnould, Laurent
Abstract : Metaplastic breast carcinoma is a rare subtype of breast cancer. This subtype is mostly found in association with poorly differentiated ductal breast carcinomas and rarely with other breast carcinoma types. We report the case of a 69-year-old woman with an exceptional invasive lobular breast carcinoma associated with metaplastic squamous cell bone metastasis occurring 2 years after the initial breast cancer diagnosis. Whole-exome sequencing and subsequent immunohistochemistry of the lesions were used to link the squamous cell bone metastasis of unknown origin to the primary breast carcinoma initially diagnosed. Searching for primary carcinoma when metastatic lesions of unknown origin occur can be complex. Current molecular biology techniques may help pathologists in associating metastasis with the primary carcinoma by identifying shared specific gene mutations, even when different morphological and immunohistochemical profiles are observed between the tumours.